1978
DOI: 10.1002/eji.1830080403
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nature of the cell surface antigen reacting with cytolytic T lymphocytes in murine oncornavirusinduced tumors

Abstract: Laboratoire d'lmmunologie et de Virologie des Tumeurs, INSERM U 152, Hgpital Cochin, ParisThe nature of the target antigen, expressed on murine sarcoma virus (MSV) and related murine tumors which reacts with T killer lymphocytes, remains ill-defined. The experiments reported here show that: (a) the previously described H-2 restriction phenomenon is found under all experimental conditions including 3-4 and 16-20-h chromium release tests. With 16-20 h tests and highly efficient T lymphocytes however, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…We found similar results with P8 15 (results not shown) as previously reported by Germain et al [24]. Moreover, an exclusive involvement of the product(s) of one region of the MHC has previously been observed in t h e interaction of anti-MSV or anti-FLV-CTL and syngeneic FMR' lymphomas [23]. It is remarkable, however, that the reactions directed against FMR' lymphomas of the same H-2d haplotype involved exclusively H-2Kd and not H-2Dd antigens [23].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found similar results with P8 15 (results not shown) as previously reported by Germain et al [24]. Moreover, an exclusive involvement of the product(s) of one region of the MHC has previously been observed in t h e interaction of anti-MSV or anti-FLV-CTL and syngeneic FMR' lymphomas [23]. It is remarkable, however, that the reactions directed against FMR' lymphomas of the same H-2d haplotype involved exclusively H-2Kd and not H-2Dd antigens [23].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, an exclusive involvement of the product(s) of one region of the MHC has previously been observed in t h e interaction of anti-MSV or anti-FLV-CTL and syngeneic FMR' lymphomas [23]. It is remarkable, however, that the reactions directed against FMR' lymphomas of the same H-2d haplotype involved exclusively H-2Kd and not H-2Dd antigens [23]. Regardless of its significance, this suggests that the functional association of H-2 and tumor antigens may depend on both the host H-2 [23] and the viral antigen (this study).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Remarkably, during the preparation of this paper, we found that two other tumor cell lines in our laboratory express the canonical EL4 V␤12 transcript. One is a line of the E&K1 tumor (77), and the other a line of MBL2, a tumor that has previously been reported to express Ly49 molecules (39), and which was derived at the same time and in the same laboratory as RBL5 (78). (A third line, E( G2 (81), was found to express a V␤12-containing receptor but this was associated with a V␤12-J␤2.1 transcript that had a distinct junctional sequence from that found in EL4 lines.)…”
Section: Discussionmentioning
confidence: 99%
“…It is thus expected that syngeneic CTL responses to tumor-associated antigens on tumor cells are probably also subject to the same dual requirement for antigen plus H-2 products, and this expectation is supported by several observations (8)(9)(10). Accordingly, tumors that fail to react with syngeneic CTLs could be expected to lack either a tumor-specific antigen as has been described (11) or the appropriate H-2 products.…”
mentioning
confidence: 66%